2018
DOI: 10.1093/nar/gky1170
|View full text |Cite
|
Sign up to set email alerts
|

Hexameric assembly of the AAA+ protein McrB is necessary for GTPase activity

Abstract: McrBC is one of the three modification-dependent restriction enzymes encoded by the Escherichia coli K12 chromosome. Amongst restriction enzymes, McrBC and its close homologues are unique in employing the AAA+ domain for GTP hydrolysis-dependent activation of DNA cleavage. The GTPase activity of McrB is stimulated by the endonuclease subunit McrC. It had been reported previously that McrB and McrC subunits oligomerise together into a high molecular weight species. Here we conclusively demonstrate using size ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 68 publications
(84 reference statements)
2
19
0
Order By: Relevance
“…Negative-stain EM indicates that the Asp356Ala mutation has a higher propensity to disrupt the TgMcrB AAA hexamer than the Glu357Ala mutation (Figure 2e), consistent with their distinct functions in nucleotide binding/stabilization versus catalysis. This result mirrors the different effects on oligomerization observed when the corresponding residues (Asp279 and Glu280) were mutated in EcMcrB (Nirwan et al, 2019a). Notably, the conserved McrB consensus loop ( 409 MNxxDR 414 ) replaces Sensor I and is located close to the γ-phosphate (Figure 2 and Supplementary Data S1).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Negative-stain EM indicates that the Asp356Ala mutation has a higher propensity to disrupt the TgMcrB AAA hexamer than the Glu357Ala mutation (Figure 2e), consistent with their distinct functions in nucleotide binding/stabilization versus catalysis. This result mirrors the different effects on oligomerization observed when the corresponding residues (Asp279 and Glu280) were mutated in EcMcrB (Nirwan et al, 2019a). Notably, the conserved McrB consensus loop ( 409 MNxxDR 414 ) replaces Sensor I and is located close to the γ-phosphate (Figure 2 and Supplementary Data S1).…”
Section: Resultssupporting
confidence: 65%
“…Previous studies reported that EcMcrBC complexes form tetradecameric assemblies in vitro (Nirwan et al, 2019a; Panne et al, 2001). In our hands, dimeric McrBC complexes generated using the full-length Tg and Ec proteins exhibit a high degree of conformational variability, which prevented us from calculating interpretable maps for these larger oligomeric states and limited our ability to analyze the dimer interface between the two McrC subunits.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…McrB is unique among AAA+ proteins as it hydrolyzes GTP rather than ATP 1 . In the presence of GTP, monomeric McrB oligomerize to hexamers 13 . Furthermore, upon binding of the endonuclease McrC, a higher oligomeric form—tetradecamers of 12 McrB and 2 McrC protomers—is formed 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of GTP, monomeric McrB oligomerize to hexamers 13 . Furthermore, upon binding of the endonuclease McrC, a higher oligomeric form—tetradecamers of 12 McrB and 2 McrC protomers—is formed 13 . The McrB GTPase activity is very low and is stimulated ~30-fold by McrC 3,13 .…”
Section: Introductionmentioning
confidence: 99%